SEMIOTICS ANALYSIS OF GENDER DIFFERENCES PORTRAYED IN BARBIE FILM - Achmad, Dita Maharani; Burhamzah, Muftihaturrahmah (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This research aims to analyse gender differences between men and women in Barbie film by using Roland Barthes’(1968 & 1972) theory of semiotics signs which are classified into denotation, connotation, and myth. This research used a descriptive qualitative method where the data taken from the scenes and the dialogues from the film. The scenes are examples of non-verbal signs while the dialogues are examples of verbal signs. Furthermore, the research is also supported by theory of gender performativity from Judith Butler (1999). Performativity is a repetitive act as a human (men or women) to present themselves. Through 20 instances, the result of this study explores the gender differences conveyed by physical appearance, activities, roles, and characteristics of women and man characters in Barbie film. From a semiotics lens, the result of this study sheds light on the way gender stereotypes are represented in modern youth-oriented film and highlight how visual representation, cultural narratives, and gender identity interact in popular media.